2017
DOI: 10.1002/jssc.201700522
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds of Shuang-Huang-Lian prescription and an insight into its binding mechanism by β2-adrenoceptor chromatography coupled with site-directed molecular docking

Abstract: Owing to the promising clinical efficacy and relatively simple composition, Shuang-Huang-Lian prescription is widely prescribed for the treatment of acute upper respiratory tract infection and acute bronchitis in practice. This necessitates the understanding of the bioactive compounds of the prescription and their binding mechanism to β -adrenoceptor, which mediates the aforementioned ailments. In this work, a column containing immobilized β -adrenoceptor was prepared using a diazonium salt reaction. The bioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Our group proposed a concept-guided methodology named as receptor chromatography (Li et al, 2015; Wang et al, 2017a; Zeng et al, 2018) to address the limitations of the above assays. In most cases, this method has immobilized the main target like G-protein-coupled receptor of approved drugs onto solid support to achieve column using the immobilized target as stationary phases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group proposed a concept-guided methodology named as receptor chromatography (Li et al, 2015; Wang et al, 2017a; Zeng et al, 2018) to address the limitations of the above assays. In most cases, this method has immobilized the main target like G-protein-coupled receptor of approved drugs onto solid support to achieve column using the immobilized target as stationary phases.…”
Section: Resultsmentioning
confidence: 99%
“…by β 2 -AR chromatography. Wang et al (2017a) analyzed Shuang-Huang-Lian prescription and identified chlorogenic acid as the bioactive compound. This work utilized β 2 -AR chromatographic method for the pursuit of bioactive compounds targeting the receptor from the aqueous extract of LHG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, the reduction in neutrophil infiltration and excessive levels of inflammatory mediators alleviate pulmonary cellular injury (29). Screening of SHL in vitro revealed that chlorogenic acid is the main bioactive ingredient that specifically binds to β2-adrenoceptor (30), which participates in smooth muscle relaxation and bronchodilation.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Affinity chromatography (AC) [7–10] is an extension of LC that employs various biomacromolecules‐coated supports as the stationary phase. This technique combines the separation capacity of chromatography and the specificity of receptor‐ligand binding, which makes the targeted screening of potentially bioactive compounds in a reliable, fast, and high throughput manner, thus widely applicable in analyzing bioactive compounds interacting with the specific target from complex samples [11–15].…”
Section: Introductionmentioning
confidence: 99%